Nocardia yunnanensis sp. nov., an actinomycete isolated from a soil sample. Issue 10 (24th July 2019) - Zhang, Jian-Xin; Ming, Hong; Zhao, Zhuo-Li; Ji, Wei-Li; Chang, Xu-Lu; Zhang, Ling-Yu; Cheng, Li-Jiao; Meng, Xiao-Lin; Li, Wen-Jun; Nie, Guo-Xing
Abstract : A novel actinomycete strain, designated CFH S0054 T, was isolated from a soil sample collected from Xiaokongshan in Tengchong, Yunnan Province, in south-west PR China. Phylogenetic analysis based on its 16S rRNA gene sequence indicated that strain CFH S0054 T belonged to the genus Nocardia . Based on the results of 16S rRNA gene sequence analysis, strain CFH S0054 T was most closely related to Nocardia concava IFM 0354 T (98.3 %), Nocardia inohanensis NBRC 100128 T (97.9 %), Nocardia otitidiscaviarum NBRC 14405 T (97.9 %) and Nocardia heshunensis CFH S0067 T (97.8 %). Strain CFH S0054 T contained C16 : 0, C18 : 1 ω9 c, C18 : 0 10-methyl (TBSA) and summed feature 3 as major cellular fatty acids and MK-8 (H4ω-cycl) as the major respiratory quinone. The polar lipid profile included phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and unknown phospholipids. The cell wall contained meso -diaminopimelic acid, and the whole-cell hydrolysates were arabinose, galactose, glucose, fructose, ribose and mannose. The genome of strain CFH S0054 T was 7.9 Mbp with a G+C content of 68.4 mol%, the average nucleotide identity (ANI) values between strain CFH S0054 T and N. concava IFM0354 T were low (ANIm<87.7 % and ANIb=84.1 %). On the basis of phylogenetic, physiological and chemotaxonomic data, strain CFHS0054 T is considered to represent a novel species of the genus Nocardia, for which the name Nocardia yunnanensis sp. nov. is proposed, The type strain is CFH S0054 T (DSM 46763 T =JCM 30082 T ).